THE ANALYSIS OF SEMIOTIC SIGNS APPEARING ON A MILD “BUKAN BASA BASI” BILLBOARD CIGARETTE ADVERTISEMENT - HIDAYAT, NOFIANTO WAHYU (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Semiotics, Piercean Model, Icons, Indexes, Symbols, and A Mild cigarette advertisement Advertisement is media to deliver messages to people with the goal toinfluence them to use certain products. In this study, semiotic approach is employed to investigate the signs, symbols, icons, and indexes in A Mild “Bukan Basa Basi” billboard advertisements. This study aims at identifying (1) the semiotic signs that are used in the A Mild “Bukan Basa Basi” cigarette advertisements, and (2) the interpretation of semiotic signs in the A Mild “Bukan Basa Basi” cigarette advertisements.This study used qualitative approach in the form of document analysis. Thetheory employed this study is Piercean theory, which presents three sign modes,icon, index, and symbol. The data were two A Mild “Bukan Basa Basi” billboardadvertisements. The first advertisement of A Mild “Daripada Gak Dapet-dapetKerja, Mending Gak Dapet-dapet Gelar” version was published in mid 2009, andthe advertisement of A Mild “Yang Lebih Muda yang Gak Dipercaya” waspublished in the end of 2009 in Indonesia. The procedures to collect the data were downloading, observing, and listing the advertisements. Then, the writer classified the sign into icon, index, or symbol and interpreted the signs meanings appearing on the advertisements, then drew the conclusion after analyzing the data.The result of this research showed that each advertisement contains semioticsigns comprising symbol, icon, and index. The icons are found in the pictures of the billboard; the symbols are found in the logo and slogan; and the indexes are found in the expressions of characters. There are eight signs found in the first advertisement and six signs found in the second advertisement. The iconic mode appears the most in the two A Mild Bukan Basa Basi billboard cigaretteadvertisement. The interpretation of the semiotic signs is related to the theme of the advertisements.Suggestion is made for next researchers to choose the semiotic study toobtain various results. Next researchers may also conduct further studies byobserving people’s interpretation on certain advertisements.